THE DEVELOPMENT COMPETITIVENESS OF SILK INDUSTRY IN NAMANGAN REGION - Равшанбек, Ходжиматов (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: Nowadays, world’s practice shows that cluster is not only means towards to the goals of the industrial policy, but is a powerful tool for the stimulation of regional development that finally can lead to the improvement of the trade balance of region, reinforcement of the employment and etc. The article studies the necessary of cluster system, its essential features in our country. In addition, analyzed effective ways of increasing fodder base of sericulture in region Given recommendations and suggestions of the improvement of silk clusters in Namangan regions.